A Review of Legislation and Bylaws Relevant to Bullying - Stanton, Lauren; Beran, Tanya (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2009)
AbstractIn this article we review legislation and bylaws that relate to school bullying. This review focuses on the differences in how bullying is defined by researchers and legislators. It further examines how some laws identify bullying specifically, whereas others address more general acts of aggression. Some laws pertain to the school environment, while others specify the workplace environment. We also examine the role of bylaws in addressing bullying. We conclude that bullying is often absent from legislation, and when it is included its definition varies across jurisdictions and/or omits non-physical forms.